Exploring Patterns of Collective Corruption and Integrity Risks by Regional Heads in Indonesia - Mohammad Hidayaturrahman; Astriana Baiti Sinaga; Ahmad Hasan Ubaid; Anak Agung Putu Sugiantiningsih; Elazhari Elazhari; Sudarman Sudarman (Journal of Governance and Public Policy, 2025)
This study aims to analyze the collective corruption networks involving regional heads in Indonesia. Employing a descriptive qualitative approach, data were gathered from secondary sources, including major national online media outlets such as Kompas, Tempo, CNN Indonesia, Antara, Detik, Liputan6, Tribun, and Jawapos. The data were analyzed through content analysis, focusing on news reports concerning regional head corruption cases from 2005 to 2023—a period marked by the implementation of direct regional elections. The findings reveal a growing phenomenon of collective corruption in which regional heads and business actors engage in collusion, forming new oligarchic power structures at the local level. This model of collective corruption encompasses both internal and external networks. Internal networks include the regional head’s family members and close staff, while external networks involve entrepreneurs and legislative representatives such as members of local parliaments. Empirically, the study identifies a pattern of systemic corruption facilitated by political actors who collaborate across government and business sectors. Theoretically, the research contributes to the evolving discourse on collective corruption by illustrating how corruption becomes institutionalized and deeply embedded in local governance structures. Regional heads emerge as central actors, establishing corruption networks that divert public funds—particularly from the Regional Budget and Revenue and Expenditure allocations—to serve private interests and consolidate political power. The novelty of this research lies in its identification of the dual role played by both private entrepreneurs and bureaucratic elements in financing corrupt practices. Moreover, it highlights how family members and staff serve as intermediaries in the process of fund misappropriation, enabling the entrenchment of corruption at the local level.